Day 3 Thu, August 13, 2015 2015
DOI: 10.2118/174603-ms
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Inhibitors: A New Route to Mitigate Adsorption in Chemical Enhanced Oil Recovery

Abstract: In this paper, we present a new route to mitigate surfactant retention in chemical EOR projects. Surfactants retention, either through adsorption on reservoir rocks or phase trapping, is one of the main constraints to achieve high performance and economical chemical EOR. Specific injection strategies thus need to be developed to mitigate surfactants retention. The use of alkaline and/or salinity gradient approaches present the disadvantage of being restricted to very specific conditions. For example, in hard b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Surfactant adsorption and loss have been studied extensively (Ahmadall et al 1993;Lv et al 2011;Somasundaran and Zhang 2006). Due to high surfactant costs, surfactant adsorption is considered as one of the key processes which define the overall chemical EOR performance and its economic feasibility by determining the total amount of surfactant required for the EOR process (Lefebvre et al 2012;Tay et al 2015). Many factors may affect the adsorption process such as oil saturation, rock mineralogy, especially clay contents, reservoir temperature, the salinity of formation water, divalent cations, ion exchange process and surfactant structure.…”
Section: Surfactant Adsorption Process On Carbonates and Its Mitigatimentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactant adsorption and loss have been studied extensively (Ahmadall et al 1993;Lv et al 2011;Somasundaran and Zhang 2006). Due to high surfactant costs, surfactant adsorption is considered as one of the key processes which define the overall chemical EOR performance and its economic feasibility by determining the total amount of surfactant required for the EOR process (Lefebvre et al 2012;Tay et al 2015). Many factors may affect the adsorption process such as oil saturation, rock mineralogy, especially clay contents, reservoir temperature, the salinity of formation water, divalent cations, ion exchange process and surfactant structure.…”
Section: Surfactant Adsorption Process On Carbonates and Its Mitigatimentioning
confidence: 99%
“…The associated problems with this approach are the possibility of inappropriate mixing of brines in the reservoir, availability of low-salinity brine in the field and logistic issues. It is also important to note that the salinity gradient effect has not been studied in carbonate rocks (Tay et al 2015).…”
Section: Surfactant Adsorption Process On Carbonates and Its Mitigatimentioning
confidence: 99%
See 1 more Smart Citation
“…Le et al (2008) dissolved the surfactant into the dense CO 2 phase instead of the brine and found its overall oil recovery was evidently higher than that of surfactant-alternating-gas injection or continuous gas injection; Kutay and Schramm (2004) reported the encouraging performance of the PolymerEnhanced Foam (PEF) and pointed out its foam durability could be considerably improved by increasing the bulk phase viscosity and thus reducing the rate of liquid drainage; Worthen et al (2013) developed a novel approach stabilizing the foam with nanoparticles such as silicon and they considered this method as a promising alternative to the conventional surfactant-stabilized foam; Majidaie et al (2012) investigated the performance of the Chemically Enhanced Water Alternating Gas (CWAG) flooding by using a commercial chemical flood simulator; Tay et al (2015) and other researchers introduced and validated the effectiveness of the so called adsorption inhibitor which was capable of significantly mitigating the surfactant loss in reservoirs. Nevertheless, each of these proposed techniques can only tackle one problem of the foam flooding (either the foam stability or surfactant retention), little work has been conducted managing to address both issues.…”
Section: Résumé -éValuation Et Optimisation D'une Technique De Rah Hymentioning
confidence: 99%
“…Thus, low surfactant retention is the key to low cost CEOR so much attention has been focused on this area of research. Recent studies of surfactant retention have been reported by Zhang and Somasundaran (2006), Solairaj et al (2012), ShamsiJazeyi et al (2014aShamsiJazeyi et al ( , 2014b, Southwick et al (2014), Levitt et al (2015), Tay et al (2015), van den Pol et al (2015) and van der Lee et al (2015). Surfactant retention is caused by both adsorption on the rock surface and trapping of a surfactant-rich phase.…”
Section: Introductionmentioning
confidence: 96%